SISTEM PENDUKUNG KEPUTUSAN PENERIMA BANTUAN KELUARGA HARAPAN KHUSUS LANSIA DENGAN MENERAPKAN VIKOR (STUDI KASUS: DESA PATUMBAK II) - Pardede, Swandi Dedi Arnold; Mesran, Mesran; Panjaitan, Melda; Waruwu, Fince Tinus; Ramadhan, Puji S (STMIK Budi Darma, 2018)
The development of Indonesias population at this time is very rapid so that Indonesia has many problems including poverty problems that occur in the midst of society. In dealing with these problems the government has a program with a form of social assistance known today as the Elderly Family Hope Program (PKH). In accordance with the Decree of the Director General of Social Protection and Security Number 26 / LJS / 12/2016 in terms of social assistance the Recipients are those that have been determined by the Director General of Social Family. As well as in the Distribution this assistance is distributed in four stages one Year. Decision Support System is a computer-based system consisting of several components, namely language system components, system components of knowledge, and problem processing system components that are interrelated with one another, in making decisions through the use of data. data and decision models in order to solve a problem. The VIKOR method where this method focuses on ranking and chooses from an alternative set and determines the solution to the problem of criteria that are constrained and can result in decision making as a final decision and the best ranking method is the lowest resultKeywords: Decision Support System, Vikor, Recipient of Family Hope AssistanceÂ